Stoneflies (Insecta: Plecoptera) from Serra Bonita, Bahia, Brazil: New species and updated records - Duarte, Tácio; Lecci, Lucas S.; Calor, Adolfo R. (Zootaxa, 2014)
There are 176 species representing eight genera and two families of Plecoptera known from Brazil. However, only ten of these species are recorded from the State of Bahia. In this study, an inventory of stoneflies from the southern region of Bahia State, Serra Bonita, including the municipality of Camacan, was undertaken from 2007–2012. Stoneflies were collected using UV light pan traps, Malaise traps, and aerial nets. One new gripopterygid species, Tupiperla bispoi n. sp., is described and illustrated. Four genera representing ten other species are recorded: Gripopteryx cancellata, G. clemira, G. garbei, G. pinima, Paragripopteryx sp., and Tupiperla tessellata (Gripopterygidae), Kempnyia alterosarum, K. gracilenta, K. jatim, and K. neotropica (Perlidae). With the present study, the number of known species of stoneflies recorded from Bahia State is 17, ten of these recorded from the Serra Bonita region.